FINANCIAL MANAGEMENT FOR BUSINESS PLAYERS AND EMPLOYEES OF BERYL’S CHOCOLATE AND CONFECTIONERY SDN BHD (SERI KEMBANGAN) - Junita Putri Rajana Harahap; Anggia Sari Lubis; Mesrawati; Juliana Br Sitompul; Tarishah Hatim Faqih; Nurul Syakirah binti Nazri (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This study is the result of community service activities carried out in Beryl’s Chocolate and Confectionery Sdn. Bhd. The focus of this service activity is employees and business players. Financial issues are often become a big problem for employees and business players. Doing business is not only a matter of getting money, but also controlling and spending it. The methods used in implementing the service are socialization, mentoring with an individual approach, training and evaluation regarding mastery of financial management and budgeting. The aim of this service activity is to implement good financial management in order to be able to manage finances well and to review sources of income and expenditure in the business. Employees and business players actors must have financial literacy regarding budgets in order to help employees and business players’s manage financial funding sources well. Financial management and is a must for employees and business players to be able to manage finances well and healthily so that long-term business sustainability. Therefore, the solution offered to solve this problem is training on how to make a budget and financial management by financial statement.